Competency for Successful Thai Farmers - Chochunya, Pinyapron; Pakasat , Nucharee (Ph.D. in Social Sciences Journal, 2021)
Objective of this research is to study the competency for successful Thai farmers with qualitative research method. There are 29 people from three sampling sets in this study (1) 18 farmers with outstanding awards from Kasetsart University (2) Seven representatives from related farming organizations for example president of Thai farmer associate, president of Thai farmer network, president of sustainable agriculture network, academics and experts from department of agricultural extension, national farmer council, and academics from rice department (3) four academics i.e. agricultural expert in sufficient economy, senior academic from Knowledge Network Institute of Thailand, agricultural expert in agricultural contribution, and the director of Chaipattana foundation. The in-depth and semi-structured interview is applied in this study in order to obtain inputs for the qualitative synthesis and able to draw. The summary as follow: There are three necessary competencies for Thai farmers to be successful. (1) Eight areas of knowledge i.e. continuous knowledge, rice seeds, sufficient farming, organic farming/ integrated farming/new theory agriculture, natural fertilizer, lands and soils, natural reservoir/ irrigation, and adaptively of changes (2) 10 areas of skill i.e. management, accounting, marketing, planning, resources management, labor management, agricultural outbreak, environment, information technology, and equipment repair and maintenance (3) two kinds of trait and personality which are care for lands and belief in farming occupation. In addition, taking the sufficient economy concept to develop Thai farmers is also a crucial factor for being successful. Bringing innovation to apply to traditional farming knowledge lead to betterment of living quality of the Thai farmers.